Escalating schedules of incentives increase physical activity with no differences between deposit and no‐deposit groups: A systematic replication. Issue 1 (1st December 2022) - Batchelder, Sydney R.; Van Heukelom, Justin T.; Proctor, Kaitlyn; Washington, Wendy Donlin
Abstract : Physical inactivity has increasingly affected public health in the United States during the COVID‐19 pandemic as it is associated with chronic diseases such as arthritis, cancer, and heart disease. Contingency management has been shown to increase physical activity. Therefore, the present study sought to evaluate the effects of an escalating schedule of monetary reinforcement with a reset contingency on physical activity, as compared between 2 counterbalanced groups in which a monetary deposit of 25 was either required (deposit group) or not (no‐deposit group). Twenty‐five adults wore Fitbit accelerometers to monitor step counts. An ABA reversal design was used; in the 2 baseline phases, no programmed contingencies were in place for step counts. During intervention, step goals were set using a modified 70 th percentile schedule with a 7‐day window: Reaching the first goal would result in 0.25, and incentives increased by 0.25 for each subsequent day in which the goal was met. Failure to reach a goal resulted in a reset of the monetary incentive value to 0.25. Ten out of 12 participants from the deposit group were determined to be responders to intervention, whereas 8 out of 13 participants from the no‐deposit group were determined to be responders to intervention. Overall, there were no significant differences between the groups' step counts. However, the deposit group's intervention was cheaper to implement, which suggests that deposit contracts are a viable modification for physical activity interventions.